PERBEDAAN SIFAT MEKANIK KAWAT ORTODONTIK JENIS BAJA TAHAN KARAT AKIBAT PENGARUH STRUKTUR MIKRO (Studi in-vitro) - Siti Triaminingsih (Faculty of Dentistry, Universitas Indonesia, 2015)
The orthodontist has chosen the stainless-steel as a wire of choice that has a great property in elastic deformity and formability. However, some stainless-steel orthodontic wire that was found has low formability. The degree of plastic deformation during the drawing process will affect the microstructure and then to the mechanical properties of the wire. The purpose of this study was to prove that the mechanical properties of the stainless-steel orthodontic wire affected by their microstructure. The microstructure was evaluated before and after being annealed at 1050oC, and the grain size was measured from the annealed samples. Six sample of two stainless-steel orthodontic wires (RMO and Wilcock) were used to determine their tensile strength by using the universal testing machine. The area of the surface fracture was measured to determine the ductility. The wire hardness was tested by using the Micro Vickers Hardness Tester. The results showe that the Wilcock wire has a smaller grain size, higher hardness number, and higher tensile strength, but lower in ductility. In conclusion, the Wilcock wires have a lower formability than the RMO wires.